Growth promotion policies when taxes cannot be raised - Katsunori Minami; Ryo Horii (Osaka University, Institute of Social and Economic Research (ISER), 2024)
This paper examines the effect of growth-enhancing policies in an R&D-based endogenous growth model when the government does not have the ability to raise taxes to finance the required expenses. We show that the government can increase the economic growth rate by debt-financed R&D subsidies while perpetually rolling over the debt, if the productivity of research workers in product development is higher than a threshold. If the condition is not met, the government debt becomes unsustainable, or the growth rate is reduced by subsidy.
Keywords: O38; O41; 330; Economic Growth; Endogenous Growth; Public Debt; Ponzi Scheme; Research Subsidy